Factor structure of the youth psychopathic traits inventory: using the total score, three scale scores, and/or 10 subscale scores - Pihet, Sandrine (Criminal justice and behavior, 2014)
The Youth Psychopathic Traits Inventory (YPI) assesses psychopathic traits cost-effectively while minimizing social desirability. To determine which YPI summary scores should be used, we tested (a) the factorial validity of its three scales and 10 subscales, (b) the fit of a new bifactor model, and (c) the measurement invariance of the best model across gender, age, and community/institutionalized samples. Three hundred ninety-five community adolescents (M age 15.8) and 200 institutionalized adolescents (M age 15.0) filled in the French translation of the YPI. The factorial validity of the 10 subscales was supported by confirmatory factor analysis. Model comparisons favored the new bifactor model, independent of age, gender, and community/institutionalized status. Measurement invariance was confirmed. These findings support the previous YPI validation studies conducted on the 10 subscale scores, and suggest that YPI users should rely in all samples on the simultaneous use of the total score and the three scale scores, which is a common practice.